THE EFFECT OF JOB SATISFACTION ON GENERATION Y EMPLOYEES’ PERFORMANCE WITH MOTIVATION AS THE INTERVENING VARIABLE AT THE GENERAL SECRETARIAT OF THE MINISTRY OF AGRICULTURE - Indriani A.S.; Panjaitan N.K.; Kuswanto S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
In order to achieve an organization’ goal, the employees should provide maximum performance. Instead of only one generation, an organization is usually filled with several generations; one of them is the generation Y. More generations Y start to enter the job world while bringing values different from their previous generation. In order to overcome such problem, human resource development should be prepared soon, in which the excessive number of productive age population can be used to improve the development. Based on the facts above, this research aimed to analyze the effect of Job satisfaction on performance with motivation as the intervening variable. The respondents of this research are the General Secretariat of The Ministry of Agriculture employees who belong to the generation Y with the age range of 23-37 years old. There were 74 employees act as the respondents of this research taken from the accidental sampling method. The method used in this research was Structural Equation Model (SEM) through Partial Least Square (PLS) approach using the application of Smart PLS 2.0. The result of this research obtained that the employees’ job satisfaction positively and significantly affect the employees’ performance through their motivation. Motivation can function as an intervening variable to affect the employees’ job satisfaction on their performance in which the higher the generation Y employees’ job satisfaction, the more increase their motivation which gives positive and direct effect on improving their performance in the Secretariat General of the Ministry of Agriculture.